Can we identify the salt-cocrystal continuum state using XPS? - Tothadi, Srinu; Shaikh, Tabrez Rafique; Gupta, Sharad; Dandela, Rambabu; Vinod, Chathakudath P.; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
X-ray photoelectron spectroscopy (XPS) is used to understand the nature of acid-base crystalline solids, to know whether the product is a salt (proton transfer, O-center dot center dot center dot H-N+) or a cocrystal (neutral adduct, O-H center dot center dot center dot N). The present study was carried out to explore if intermediate states of proton transfer from COOH to nitrogen (the proton resides between hydrogen bonded to O and N, O center dot center dot center dot H center dot center dot center dot N, quasi state) can be differentiated from a salt (complete proton transfer, N+-H center dot center dot center dot center dot O-) and cocrystal (no proton transfer, O-H center dot center dot center dot N) using N 1s XPS spectroscopy. The intermediate states of proton transfer arise when the pK(a) difference between the acid and the conjugate base is between -1 and 4, -1 < Delta pK(a) < 4, a situation common with COOH and pyridine functional groups present in drug molecules and pharmaceutically acceptable coformers. Complexes of pyridine N bases with aromatic COOH molecules in nine salts/cocrystals were cocrystallized, and their N 1s core binding energies in XPS spectra were measured. The proton state was analyzed by single-crystal X-ray diffraction for confirmation. Three new complexes were crystallized and analyzed by XPS spectra (without knowledge of their X-ray structures), to assess the predictive ability of XPS spectra in differentiating salt-cocrystal intermediate states against the extremities. The XPS results were subsequently confirmed by single-crystal X-ray data. Complexes of 3,5-dinitrobenzoic acid and isonicotinamide in 1:1 and 1:2 ratios exist as a salt and a salt-cocrystal continuum, respectively, as shown by the N 1s core binding energies. The proton states of the crystalline solids by XPS are in good agreement with the corresponding crystal structures. Other complexes, such as those of 3,5-dinitrobenzoic acid with 1,2-bis(4-pyridyl)ethylene, exhibit a salt-cocrystal continuum, maleic acids with 1,2-bis(4-pyridyl)ethylene and acridine are salts, 2-hydroxybenzoic acid and acridine is a salt, and the complex of 3,5-dinitrobenzoic acid and 3-hydroxypyridine is a salt and salt-cocrystal continuum, while fumaric acids with 1,2-bis(4-pyridyl)ethylene and acridine are cocrystals. Furthermore, three new acidbase complexes of 3,5-dinitrobenzoic acid with phenazine, 4-hydroxypyridine, and 4-cyanopyridine were studied initially by XPS and then confirmed by X-ray diffraction. In summary, since the N 1s binding energies cluster in a narrow range as cocrystals (398.7-398.9 eV) and salts (400.1-401.1 eV), it is clearly possible to differentiate between cocrystals and salts, but the saltcocrystal continuum values in XPS spectra are clustered in an intermediate range of cocrystals and salts but overlap with those of cocrystal or salt binding energies.

Carbazole substituted amidinato silylene: synthesis, bonding, and coordination behavior with coinage metals - Ghosh, Moushakhi; Tothadi, Srinu; Khan, Shabana (Organometallics, 2021)
In this work, the synthesis and characterization of a new carbazole substituted amidinatosilylene (1) and its coinage metal complexes 3-8 are being reported. Before the complexation reactions, we prepared [PhC(N+Bu)(2)Si(Cbz)-> Co(CO)Cp] complex (2) to estimate the sigma-donating strength of the newly synthesized silylene 1. Further, several commonly available coinage metal salts were utilized for the complexation reactions with 1, which afforded complexes 3-8. The solid-state structures of 1-8 have been validated by single-crystal X-ray diffraction studies, NMR spectroscopy, and mass spectroscopy. DFT studies were also performed to understand the bonding scenario of 1 and 3-7. Of note, 1 consists of a HOMO on its carbazolide moiety, and the HOMO-1 features the silylene character. We also compared the HOMO-LUMO gap of 1 with other amidinato silylenes having different N-substitutions.